2020
DOI: 10.3174/ajnr.a6557
|View full text |Cite
|
Sign up to set email alerts
|

MRI Signal Intensity and Electron Ultrastructure Classification Predict the Long-Term Outcome of Skull Base Chordomas

Abstract: BACKGROUND AND PURPOSE: MR imaging is a useful and widely used evaluation for chordomas. Prior studies have classified chordomas into cell-dense type and matrix-rich type according to the ultrastructural features. However, the relationship between the MR imaging signal intensity and ultrastructural classification is unknown. We hypothesized that MR imaging signal intensity may predict both tumor ultrastructural classification and prognosis.MATERIALS AND METHODS: Seventy-nine patients with skull base chordomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Therefore, in this study, the SIR was used as a quantitative parameter to eliminate the influence of different MRI scanners and imaging parameters on the results. Similar to our study design, the SIR also showed potential for differential diagnosis in other scenarios (12,(24)(25)(26). However, different from previous studies, we used an external test cohort to further clarify the actual diagnostic performance of the SIR.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, in this study, the SIR was used as a quantitative parameter to eliminate the influence of different MRI scanners and imaging parameters on the results. Similar to our study design, the SIR also showed potential for differential diagnosis in other scenarios (12,(24)(25)(26). However, different from previous studies, we used an external test cohort to further clarify the actual diagnostic performance of the SIR.…”
Section: Discussionmentioning
confidence: 85%
“…Some of the factors that influence survival time in patients with chordoma include age, tumor size, histological type, tumor grade, and metastasis have been widely reported [ 7 , 24 , 25 ]. As research into chordoma continues, more and more prognostic factors such as imaging [ 26 , 27 ], genetics [ 28 , 29 ], and biomarkers [ 30 , 31 ] have been explored for use in the survival analysis of chordoma patients. The limitations of linear relational models based on the traditional CoxPH model have become increasingly apparent in the face of the massive amount of multidimensional data [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the limited phenotypic characterization of SBC prevents an optimal patient stratification to improve treatment outcomes. In this context, the growing availability of imaging data can be favourably exploited as a source of prognostic factors [ 8 , 9 ], with studies in the literature supporting the predictive power of the appearance of chordomas on diagnostic imaging, such as CT and MRI [ 10 ]. More recently, qualitative imaging factors are being complemented by quantitative ones, such as radiomic features [ 11 ].…”
Section: Introductionmentioning
confidence: 99%